Evaluasi Kebijaksanaan Industri Persusuan di Indonesia - nFN Erwidodo; Fadhil Hasan (Jurnal Agro Ekonomi, 1993)
The Indonesian dairy sector remains subject to tight regulations, which all aimed at fostering the development of local dairy industry and protecting it from possible unfair overseas competition. There are four principal regulations that directly influence the development of domestic dairy industry, namely the import ratio requirement (BUSEP), import tariffs, an import licensing scheme, and investment restrictions in milk processing. The study shows that the current policy-mix has improved the growth performance of domestic dairy industry, indicated by the significant increased in dairy cattle population, dairy farmers, fresh milk production and the production of dairy end-product as well. In particular, the import ratio requirement (BUSEP) appears to be very effective in fostering domestic milk production and protecting dairy farmers' income, since it provides guarantee that all domestic fresh milk will be absorbed by milk processor at reasonable prices. The analysis, however, indicates that the current policies have contributed potential negative impacts and costs to the economy paid by domestic dairy consumers. The domestic consumers could enjoy considerably larger benefits if less trade restrictions are imposed. Moreover, it is also found that the benefits of protection are mostly enjoyed by milk manufacturer. The authors suggest that gradual movement towards a more deregulated dairy industry is a necessary condition to increase efficiency and strengthen Indonesia's competitive capability in the world market. Abolishing import licensing and gradually reducing import tariffs on dairy products are two crucial policy reforms, besides other direct efforts for increasing efficiency of the industry.